Smartphone-Interlocked Advanced Driver Assistance System Development for Safety - Lee, DongIn; Kim, Bonghwan; Leul Lee, Byeung; Chun, Kyunghan (International Journal of Engineering and Technology, 2018)
In this paper, we propose new advanced driver assistance system (ADAS) that interfaces with smartphones. The proposed system consists of a heads-up-display (HUD) and a driving information rear display (DIRD), and this configuration outputs information from the ADAS into the front and rear windshields. The HUD and DIRD help drivers operate their vehicles safely. In particular, the HUD and DIRD are constructed by combining navigation information provided by a smart phone and vehicle maintenance information, where vehicle information is provided by the electronic control unit (ECU). Experimental results show that the ADAS can be improved by providing the driver with the necessary safe driving information, and the vehicle can be easily maintained using the information obtained directly from the ECU.Â Â